Clinical outcomes of endoscopic balloon dilatation of intestinal strictures in patients with Crohn's disease. Issue 35 (August 2019) - Winder, Ophir; Fliss-Isakov, Naomi; Winder, Gilad; Scapa, Erez; Yanai, Henit; Barnes, Sophie; Dekel, Roy; Dotan, Iris; Maharshak, Nitsan
Abstract : Abstract: Intestinal strictures are common complications of Crohn's disease (CD). Endoscopic balloon dilatation (EBD) constitutes an alternative therapy to surgery, but associated factors of procedure success are inconclusive. Therefore, we aimed to evaluate the EBD success rate and its associated factors in CD patients. This is a retrospective cohort study of consecutive EBDs that were conducted between 2006 and 2014 among patients with CD with lower gastrointestinal tract strictures. Patients' and stricture characteristics, short term procedure success and related complications at 1 week follow-up, and long-term clinical endpoints were documented. A total of 138 dilatations were performed on 64 CD patients. The overall dilatation success rate was 84.8%, with no difference between primary or anastomotic strictures, or between first or recurrent dilatation procedures. Long strictures (≥4 cm) were negatively associated with successful EBDs, but not with perforations. A multivariate analysis adjusting for age, sex, smoking, and disease duration revealed that a maximal dilatation diameter of ≥15 mm was positively associated with a successful EBD, while an inflamed stricture was negatively associated with procedure success. Strictures which were both long and inflamed were associated with the lowest EBD success rates compared with other strictures. Only 32.8% of patients required surgery during the follow-up period. Long-term prevention of surgery was negatively associated with stricture length and with a successful EBD. EBD is highly successful in treating intestinal strictures and in prevention of surgery in CD patients. Although EBD of long strictures is safe, it will not prevent surgery in the majority of cases.